Sustainable internet Third Asian Internet Engineering Conference, AINTEC 2007, Phuket, Thailand, November 27-29, 2007 : proceedings - Asian Internet Engineering Conference (Computer Communication Networks and Telecommunications, 2007)
Invited talk 1 -- Packet forwarding in pocket switched networks – An empirical characterization of human mobility -- Session 1: Wireless networks -- Mobility versus density metric for OLSR enhancement -- DAD-MPR flooding protocol, convergence evaluation through simulation -- A prototyping environment for wireless multihop networks -- Efficient selection of multipoint relays in wireless ad hoc networks with realistic physical layer -- Invited talk 2 -- Mobile hotspots -- Session 2: Mobility management -- Extending home agent migration to mobile IPv6 based protocols -- Experimental evaluation of EAP performance in roaming scenarios -- Session 3: Packet transmission -- Unidirectional lightweight encapsulation with header compression for IP based satellite communication over DVB-S -- Analysis of FEC function for real-time DV streaming -- Invited talk 3 -- Ubiquitous devices, mobility and context awareness -- Session 4: Applications and services -- Improving the load balancing performance of reliable server pooling in heterogeneous capacity environments -- WOD – proxy-based web object delivery service -- Invited talk 4 -- Implementation issues of early application identification -- Invited talk 5 -- Securing internet coordinate systems -- Session 5: Network monitoring -- A real-time performance-monitoring tool for emergency networks -- A role-based peer-to-peer approach to application-oriented measurement platforms -- Invited talk 6 -- Gap analysis in IP multicast dissemination -- Session 6: Routing -- Can forwarding loops appear when activating iBGP multipath load sharing? -- Quality-of-service multicast overlay spanning tree algorithms for wireless ad hoc networks -- Invited talk 7 -- Architecture of satellite internet for Asia-wide digital communications.